2019
DOI: 10.1111/jar.12576
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dementia Care Mapping on well‐being and quality of life of older people with intellectual disability: A quasi‐experimental study

Abstract: BackgroundThe ageing of people with intellectual disability, accompanied with consequences like dementia, challenges intellectual disability‐care staff and creates a need for supporting methods, with Dementia Care Mapping (DCM) as a promising possibility. This study examined the effect of DCM on the quality of life of older people with intellectual disability.MethodsWe performed a quasi‐experimental study in 23 group homes for older people with intellectual disability in the Netherlands, comparing DCM (n = 113… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 62 publications
0
3
1
3
Order By: Relevance
“…Although we found that staff valued DCM in daily care practices and that indications that it might improve job performance and quality of (person-centred) care for older people with intellectual disabilities, previous research has found no evidence on the quality of life of people with intellectual disabilities nor on job satisfaction of care staff (Schaap et al, 2019a(Schaap et al, , 2019b. The effectiveness of DCM should thus be assessed in a study aimed at outcomes in the direct care process, such as job performance, quality of (person-centred) care…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Although we found that staff valued DCM in daily care practices and that indications that it might improve job performance and quality of (person-centred) care for older people with intellectual disabilities, previous research has found no evidence on the quality of life of people with intellectual disabilities nor on job satisfaction of care staff (Schaap et al, 2019a(Schaap et al, , 2019b. The effectiveness of DCM should thus be assessed in a study aimed at outcomes in the direct care process, such as job performance, quality of (person-centred) care…”
Section: Discussioncontrasting
confidence: 87%
“…Person‐centred care can yield more effective interactions between clients and care professionals (Brownie & Nancarrow, 2013; Tay et al., 2018; Van der Meer et al., 2017), and better collaboration of staff in coordination of care (Edvardsson et al., 2008; Rathert, Wyrwich, & Boren, 2013). In ID‐care, however, person‐centred methods, usually derived directly from regular dementia care, are often used in an unsystematic way (Fokkens, IJsbrandij, & Jansen, 2016; Schaap, Finnema, Stewart, Dijkstra, & Reijneveld, 2019a), even though previous research has strongly indicated that they should be customized to be successful (Hodes, Meppelder, Schuengel, & Kef, 2014; Vlaskamp, Hiemstra, & Wiersma, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The principles of person-centred care are well established within intellectual disability practices (Hakobyan et al , 2020; Mansell and Beadle‐Brown, 2004; Smith and Carey, 2013). Key to improving dementia care practice is incorporating person-centred approaches within education programmes (McGinley and Knoke, 2018; Schaap et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…DCM bleek geen effect te hebben op de kwaliteit van leven van mensen met VB (Schaap, 2019;Schaap et al, 2019b). De methodiek bleek evenmin effect te hebben op de arbeidstevredenheid en het gevoel van competentie van begeleiders (Schaap, 2019;Schaap et al, 2019a).…”
Section: Werkzaamheid Op Basis Van Kwantitatief Onderzoekunclassified